2000
DOI: 10.21236/ada405478
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fire Detection (OFD) for Military Aircraft Hangars: Final Report on OFD Performance to Fuel Spill Fires and Optical Stresses

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…In other words, the reduced mass burning rates of the thin fuel depth fires was believed to be primarily a function of the thermal properties of the substrate. This hypothesis was based upon testing conducted by Gottuk et al [2] and Putorti [3] who found that spill fire burning rates were on the order of one-fifth that of traditional pool fire burning rates. Similar findings were also reported by Garo et al [12] who attributed the reduced mass burning rates of fuels burning atop a water substrate to the ‗heat sink effect' of the water sub-layer.…”
Section: Variables Impacting Mass Burning Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, the reduced mass burning rates of the thin fuel depth fires was believed to be primarily a function of the thermal properties of the substrate. This hypothesis was based upon testing conducted by Gottuk et al [2] and Putorti [3] who found that spill fire burning rates were on the order of one-fifth that of traditional pool fire burning rates. Similar findings were also reported by Garo et al [12] who attributed the reduced mass burning rates of fuels burning atop a water substrate to the ‗heat sink effect' of the water sub-layer.…”
Section: Variables Impacting Mass Burning Ratesmentioning
confidence: 99%
“…Analysis of these datasets resulted in the conclusion that the differences between the burning rates of thin fuel layers and those reported in the literature, typically deep fuel layers, were potentially due to the differing heat transfer phenomena occurring within a deep fuel layer (k = 0.11 W/m·K) versus a thin layer atop a more conductive substrate (i.e., concrete (k = 1.4 W/m·K)). Based upon these data [3,4,11], it was concluded that unconfined fuel spills producing very thin (i.e., ≤ 1 mm (0.04 in.)) fuel depths experience greater heat losses to the substrate, thus reducing the amount of heat retained within the burning fuel layer and consequently reducing the fuel mass burning rate [6].…”
Section: Variables Impacting Mass Burning Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…In these models, it is obvious that the fuel consumption due to burning is crucial in the spread process, and the quasi-steady burning is directly determined by the burning rate of the spill fire for a certain discharge rate [9]. However, the burning rate of pool fires is directly considered that of spill fires in some cases, even though this has been proved wrong by Gottuk et.al [10] and Mealy et al [11]. They found that the burning rate of spill fires is lower than that of pool fires and in some situations the ratio of the spill fires' burning rate to that of pool fires is less than 0.5.…”
Section: Introductionmentioning
confidence: 99%